Dual Regulatory Roles of SlGAMYB1 in Tomato Development: GA-Dependent and GA-Independent Mechanisms - Fanjia Zhong; Fengpan Wang; Zike Chen; Tengbo Huang; Panpan Zhao (Plants)
The R2R3-MYB transcription factor GAMYB plays crucial roles in plant growth and development, but the biological functions of SlGAMYB1 in tomato remain poorly understood. Here, we investigated the roles of SlGAMYB1 by overexpressing a miR159-resistant version (35S:SlGAMYB1m) in tomato. Transgenic plants exhibited a dwarf phenotype with reduced internode elongation, which was associated with decreased bioactive gibberellin (GA) levels due to transcriptional repression of SlGA3ox1 and activation of SlGA2ox1/2/4/5. Additionally, 35S:SlGAMYB1m altered leaf morphology by inhibiting cell proliferation through downregulation of cell cycle genes, resulting in larger but fewer epidermal cells. Intriguingly, 35S:SlGAMYB1m plants displayed increased floral organ number, a process likely mediated by the upregulation of SlWUS rather than GA signaling. These findings demonstrate that SlGAMYB1 regulates diverse aspects of tomato development through both GA-dependent and independent pathways, providing new insights into the functional diversification of GAMYB genes and potential strategies for genetic improvement of tomato architecture and yield.